EFFECT OF TEMPERATURE VARIATIONS IN MANUAL TUBING MACHINES FOR PET PLASTIC MATERIAL ON TENSILE STRENGTH - Wijaya, Kelvin; Murdiyanto, Danang; Cristanto Putra Mbulu, Bernadus (Universitas Katolik Widya Karya Malang, 2024)
Briquettes are a type of alternative energy whose raw material source Plastic waste is an environmental problem faced by the people of Indonesia and the world. On the other hand, the production of waste generated in various institutions and sectors in Indonesia continues to increase every year, including the industrial sector whose production process is large-scale. Its use as a basic material for packaging bottles reaches 30% of world use. PET is also used as a synthetic fiber or polyester which accounts for 60% of world use. Study the author will do that is to make a tubing made from PET plastic waste that can be used as raw material for tubing. Using temperature variations (190℃, 200℃, 210℃), then 9 samples from each variation will be micro-photographed the effect of temperature on tubing results and tested for maximum tensile. After that, calculations are carried out to obtain the maximum tensile stress and strain values. Then the average maximum load value that can be received by PET tubing is highest at 190ºC temperature tubing has the ability to withstand tensile strength better than all temperature variations so that the average value is 35.94 N/mm2 and 200ºC is able to withstand 35.49 N/mm2 and 210ºC with 18.30 N/mm2. It can be interpreted that the higher the temperature, the effect on holding the tensile strength of the PET tubing and making the plastic structure change so that 210oC is close to the recycling value, while for temperatures below it is still non-recycled.